AN OBSERVATIONAL ANALYSIS OF 7,000 PATIENTS WITH SEVERE HYPERCHOLESTEROLEMIA: IDENTIFYING AN AGE-TREATMENT GAP IN CARDIOVASCULAR RISK REDUCTION - Elizabeth Jean-Marie; Nour Tashtish; Sadeer Al-Kindi; Ian J Neeland (Elsevier, 2023)
Therapeutic Area: Severe Hypercholesterolemia, Lipid Management Background: Hypercholesterolemia is an important treatable risk factor for cardiovascular disease-which remains one of the leading causes of death in the United States. Approximately 7% of American adults have severe hypercholesterolemia (a low-density lipoprotein cholesterol (LDL-C) level ≥190 mg/dL). Despite a class I indication for statin therapy, many patients remain untreated or undertreated. Methods: We reviewed all patients ≥ 18 years in our health system with at least one LDL-C level ≥ 190 mg/dL resulted within the last five years (since 01/01/2016). We explored the associations between patient demographics, lipid profile, and rate of statin prescription using logistic regression. Results: A total of 7703 had LDL-C ≥ 190 mg/dL in our Northeast Ohio health system. The mean age was 58 ± 15 years, 64% were female, and 17% were Black. Median LDL-C was 204 [IQR 195-220] mg/dL. Only 58% of patients were prescribed statin therapy. The statin prescription rate varied substantially by age, with only 28% of individuals ≤30 years receiving a statin, with prescription rates increasing with age. Younger women had lower rates of statin prescription compared with younger men, but the differences became less with older age (age*sex Pinteraction=0.02). In a multivariable model, age (OR 1.25, 95% CI [1.21 - 1.30] per 10 years, P<0.001), LDL-C (OR 1.05 [1.03-1.07] per 10 mg/dL, P<0.001), Black race (OR 1.83 [1.60-2.09], P<0.001), and coronary artery disease (OR 3.48 [2.89-4.18], P<0.001) were associated with higher likelihood of receiving a statin prescription. Conclusion: In our health system, less than two thirds of patients with severe hypercholesterolemia defined by LDL-C level ≥190 mg/dL are prescribed a statin. Statin prescription rates were highly dependent on age and to a lesser extent on sex. This finding highlights a treatment gap in preventative care, where younger patients are most vulnerable to undertreatment despite elevated cardiovascular disease risk.